Letting Silence Speak: Licia Canton’s The Pink House and Other Stories - Moyes, Lianne (Italian Canadiana, 2023)
As scholars and reviewers of Licia Canton’s The Pink House and Other Stories have pointed out, certain characters recur across the cycle of stories and certain events are retold from different perspectives. This is especially evident, I argue, in the series of stories related to a traumatizing accident in which a woman writer is pinned between two car bumpers. These stories, interspersed throughout the collection, are linked not only by continuities in character and detail but also by forms of discontinuity: breaks in the frame of fiction, non-linear narrative practices, and shifts in time and point of view. In the wake of the accident, the woman writer – who is variously a narrator and a character – confronts writer’s block and the holes in her memory, as well as all the interruptions of daily life. The stories are a study in silence, a silence that is audible at the level of the story cycle, the narration of each story, and the enunciation of each character. By foregrounding gaps in understanding and moments in which the senses say more than words, these stories prompt readers to look for – to imagine – what cannot yet be known or spoken. They point toward states of emotion and ways of making sense of the experience that might otherwise remain locked in silence.